Pensée et langage chez Karl Popper et Lev Vygotski - Alain Firode (Nantes Université, 2011)
During the last period of his career, Popper developed an evolutionary theory of mind, with conclusions that are often close to the theses of Soviet psychologist Lev Vygotski. Both authors share the idea that language and the symbolic world in general play a decisive role in the formation of the human mind. They both emphasize the importance, in the process of mental development, of the interactions between the psyche and the linguistic and cultural environment. However, Popper's theory contains an idea which is not present in Vygotski's: namely the thesis according to which the symbolic universe ("World 3") possesses an autonomous logical reality, different from the physical, psychological and social reality. This thesis, which clashes with Vygotski's Marxist and materialistic point of view, introduces a deep difference between these two theories of mind. The result of this is that the Popperian analyses, unlike these of Vygotski, are not really compatible with the constructivist paradigm which currently prevails in the field of education.